2017
DOI: 10.3389/fphar.2017.00442
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and In Vivo Profiling of a Refined Rat Model of Walker 256 Breast Cancer Cell-Induced Bone Pain Using Behavioral, Radiological, Histological, Immunohistochemical and Pharmacological Methods

Abstract: In the majority of patients with advanced breast cancer, there is metastatic spread to bones resulting in pain. Clinically available drug treatments for alleviation of breast cancer-induced bone pain (BCIBP) often produce inadequate pain relief due to dose-limiting side-effects. A major impediment to the discovery of novel well-tolerated analgesic agents for the relief of pain due to bony metastases is the fact that most cancer-induced bone pain models in rodents relied on the systemic injection of cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 105 publications
(125 reference statements)
7
27
0
Order By: Relevance
“…This mechanical hypersensitivity was spontaneously reversed at day 46 (resolved pain behaviours). These results were in agreement with our previous report describing the apparently spontaneous resolution of pain hypersensitivities in this cancer‐induced bone pain model in rats, despite the ongoing presence of cancer cells in the ipsilateral tibiae …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This mechanical hypersensitivity was spontaneously reversed at day 46 (resolved pain behaviours). These results were in agreement with our previous report describing the apparently spontaneous resolution of pain hypersensitivities in this cancer‐induced bone pain model in rats, despite the ongoing presence of cancer cells in the ipsilateral tibiae …”
Section: Resultssupporting
confidence: 93%
“…Using μCT scans, histological assessment with H&E staining, and immunohistochemical staining against Cytokeratin 18 in tibial bones, we have demonstrated that cancer cells were present in the bones and pathological changes associated with metastatic lesions such as osteolytic bone degradation was evident. This was the case both during the period when pain behaviour (< day 21) was evident and also during the period when pain behaviour was apparently resolved (> day 21), as reported in detail in our previous studies . Group of rats inoculated with live W256 cells developed significant ( P ≤ .05) mechanical hypersensitivities in the bilateral hindpaws at days 7–10 post‐inoculation (pain behaviours present), when compared to group of rats inoculated with HK W256 cells (Figure ).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations